Innovation & Entrepreneurship Competencies for Gen Z: A Systematic Literature Review - Nazarwin; Yunia Wardi; Hendrik Heri Sandi; Riki Wanda Putra (Attractive : Innovative Education Journal, 2026)
This article presents a Systematic Literature Review (SLR) on entrepreneurial competence and innovation competence/innovative behavior among Generation Z (Gen Z) in publications from 2023 to 2026. Using the PRISMA 2020 approach and a structured Scopus search, 29 eligible articles were identified and analyzed through thematic synthesis and an antecedents–mechanisms–outcomes framework. The findings highlight three dominant domains: digitally oriented entrepreneurial competence, entrepreneurial literacy and readiness, and innovation competence ranging from innovation attitudes to innovative behavior and green innovation. Key mechanisms include digital self-efficacy, entrepreneurial alertness, and mindset development, while technology/AI and sustainability shape emerging research trends. Overall, the review shows that the literature is still dominated by intention-based outcomes, indicating the need for future studies to focus more on innovative behavior, entrepreneurial action, and stronger construct and instrument consistency.